Wavelength self-calibration and sky subtraction for Fabry–Pérot interferometers: applications to OSIRIS - Weinzirl, T.; Aragón-Salamanca, A.; Bamford, S.P.; Rodríguez del Pino, B.; Gray, M.E.; Chies-Santos, A.L. (Oxford University Press, 2015)
We describe techniques concerning wavelength calibration and sky subtraction to maximize the scientific utility of data from tunable filter instruments. While we specifically address data from the Optical System for Imaging and low Resolution Integrated Spectroscopy instrument (OSIRIS) on the 10.4-m Gran Telescopio Canarias telescope, our discussion is generalizable to data from other tunable filter instruments. A key aspect of our methodology is a coordinate transformation to polar coordinates, which simplifies matters when the tunable filter data are circularly symmetric around the optical centre. First, we present a method for rectifying inaccuracies in the wavelength calibration using OH sky emission rings. Using this technique, we improve the absolute wavelength calibration from an accuracy of ∼5 to 1 Å, equivalent to ∼7 per cent of our instrumental resolution, for 95 per cent of our data. Then, we discuss a new way to estimate the background sky emission by median filtering in polar coordinates. This method suppresses contributions to the sky background from the outer envelopes of distant galaxies, maximizing the fluxes of sources measured in the corresponding sky-subtracted images. We demonstrate for data tuned to a central wavelength of 7615 Å that galaxy fluxes in the new sky-subtracted image are ∼37 per cent higher, versus a sky-subtracted image from existing methods for OSIRIS tunable filter data.